Fire loading and structural response - Chamberlain, Geoff (Technical note ;, 2009)
This technical note updates and expands certain aspects of the guidance on fire engineering and is limited to hydrocarbon fires and the response of steel members in the types of structures typically encountered in the oil and gas industry.